PORTOFOLIO SEBAGAI MODEL PEMBELAJARAN SEIMBANG DALAM PROSES BELAJAR MENGAJAR PENDIDIKAN AGAMA ISLAM DI LEMBAGA PENDIDIKAN UMUM - Ismail Fahri (Jurnal Forum Tarbiyah, 2011)
Education of Islamic Religion is a very important lessonfor fostering moral learners. However, in reality, Education of IslamicReligion is considered incapable in generating generations whoare possessing good moral, as it is alleged by education experts dueto the lack of class hours, less learning patterns of the target, as aresult of a lack of continuity in learning. Learners, in religion learningonly developed on the cognitive development, whereas other domainssuch as affective and psychomotor are virtually untouched. Therefore,the learning method of Education of Islamic religion based onPortfolio may help to develop the three domains of education and isable to increase the religious morals of children